Effect of Solution Treatment Temperature on Microstructure and Mechanical Properties of A356 Alloy - M., Ishak; Amir, Aziz; Asnul Hadi, Ahmad (Praise Worthy Prize, 2014)
Over the years, aluminum content in a vehicle part is increasing due to the needs to reduce weight as well as increase fuel efficiency. Most of the cast product in a vehicle part is mostly cast from A356 alloy. It is used because A356 alloy posses’excellent characteristics over other type of alloy such as cast ability, high weight-to-strength ratio, good corrosion resistance and good weld-ability. Most of the cast component in vehicle such as cylinder head favors hardness over tensile strength. Most of the solution treatmentsstudied was done on sample having α-Al with dendritic structure.The objective of this research is to investigate the effect of solution treatment temperature on microstructure and mechanical properties of A356 (Al7Si0.3Mg) aluminum alloy. Heat treatment was done to harness the full potential of cast A356 alloy and T6 heat treatment is the commonly used treatment for this alloy. In the present study, the specimen was cast using low pouring temperature method which produces equiaxedα-Al structure. The specimen undergone solution treatment for two (2) hours at three different temperatures (530 °C, 540 °C, and 550 °C), quenched in water at room temperature, followed artificial aged for six (6) hours at 170 °C. Mechanical properties of A356 aluminum alloy were investigated by tensile test and hardness test. The relation between size, shape, and distribution of Si particle and the alloy’s mechanical properties were investigated. Si particle size, shape, and dispersion affect the mechanical properties of cast A356 alloy. Higher solution treatment temperature produce smaller and more globular Si particle before completing T6 heat treatment. Elongations decrease while ultimate tensile strength (UTS) increase as solution temperature increased from 530 °C to 550 °C. A356 aluminum alloy specimen solution treated at 530 °C have comparable hardness compared with specimen solution treatment at 540 °C before and after artificial ageing - complete T6 heat treatment - with higher elongation and lower energy usage as added benefit.